2011
DOI: 10.1371/journal.pntd.0001408
|View full text |Cite
|
Sign up to set email alerts
|

Tools to Support Policy Decisions Related to Treatment Strategies and Surveillance of Schistosomiasis Japonica towards Elimination

Abstract: BackgroundAppropriate diagnostics to monitor disease trends and assess the effectiveness and impact of interventions are essential for guiding treatment strategies at different thresholds of schistosomiasis transmission and for certifying elimination. Field validation of these assays is urgently needed before they can be adopted to support policy decisions of the national programme for control and elimination of schistosomiasis in P.R. China. We compared the efficacy and utility of different immunoassays in gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…As the prevalence falls further below 10%, improved, easy-to-use tests will be useful to target treatment and monitor prevalence trends and effectiveness of infection control measures. 29,30 Also, there was significant variation in the implementation of control interventions in the study area, despite public health officials doing the work. Monkey Bay Community Hospital provided multifaceted control interventions for infection, unlike the mission facilities (due to limited capacity, support, supervision, and coordination between the mission facilities and the DHO).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As the prevalence falls further below 10%, improved, easy-to-use tests will be useful to target treatment and monitor prevalence trends and effectiveness of infection control measures. 29,30 Also, there was significant variation in the implementation of control interventions in the study area, despite public health officials doing the work. Monkey Bay Community Hospital provided multifaceted control interventions for infection, unlike the mission facilities (due to limited capacity, support, supervision, and coordination between the mission facilities and the DHO).…”
mentioning
confidence: 98%
“…At this lower prevalence, targeted treatment to infected people is more appropriate, given the limited availability of drugs. 29 The facilities therefore need to improve their laboratory services to diagnose schistosomiasis, using simpler tests that do not require specialised skills, training, or equipment-for example, the WHO urine chart or urinalysis reagent stripsbefore treatment initiation. As the prevalence falls further below 10%, improved, easy-to-use tests will be useful to target treatment and monitor prevalence trends and effectiveness of infection control measures.…”
mentioning
confidence: 99%
“…Mean infection intensity was 3.0 EPG (range 0-88). Of the 11 Kato-Katz positive individuals, seven had only 1-3 eggs detected (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). At the village level, S. japonicum infections were detected by Kato-Katz and the hatching test in two of the four villages, and by PCR in three of the four villages (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] The performance of immunoassays such as indirect hemagglutination assay, enzyme-linked immunosorbent assay, and dipstick dye immunoassay has recently been assessed. [8][9][10] These studies have shown that immunoassays have high sensitivities ( 90%) and ease of use when compared with coprological methods, but issues of specificity and the inability of antibody detection methods to distinguish between current and past infections are still of concern. Moreover, the sensitivity of serological testing, like coprological testing, declines as infection intensity decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the global schistosomiasis control program has made tremendous progress in terms of reducing the schistosomiasis prevalence and morbidity in many endemic countries, particularly after the London Declaration on Neglected Tropical Diseases. With the goal of the disease elimination, low but persistent levels of schistosomiasis transmission require essential changes in many aspects of elimination approaches [5]. For instance, the new tools of diagnosis and surveillance are urgent to be used in the local settings with low-intensity infections of hosts and in the evaluation of intervention effectiveness.…”
mentioning
confidence: 99%